Theological rationalism in Medieval Islam (Leuven)
x, 184 sayfa
Keywords: The present volume comprises substantially revised and enlarged versions of papers read at a conference convened in June 2010 by the ERC-Project at the German Orient-Institut in Istanbul. Under the title “Theological Rationalism in Medieval Islam: New Texts and Perspectives“, a group of leading international scholars was invited to introduce important new kalam-texts that have not been the subject of previous studies or to explore new trajectories in studying known key-texts. While most contributions combine both aspects, they are divided into two groups according to the predominating aspect. The first four contributions introduce hitherto unknown or unexplored texts and assess how these can modify and expand our understanding of kalam. The second group of contributions applies novel methodologies in order to identify and interpret historical and conceptual transformations that occurred within kalam or resulted from its interaction with other disciplines. The question whether God can delay the elucidation of vague or unclear statements raises a number of thorny theological questions. It is hoped that the results of these presentations will have an impact beyond their subject matter in that their novel approaches will find their place in the methodological toolbox of kalam scholarship, thus stimulating work that will further expand our knowledge of Muslim kalam.